An oral electrolyte solution without glucose for oral rehydration indiarrhea with mild and moderate dehydration - Rosyid R. A; Sutrisno D. S.; Harun Alrasyid; Untoro Untoro; Rien Armi U.; Moenginah P. A.; Ismangoen Ismangoen (Paediatrica Indonesiana, 1981)
For rural areas in Indonesia where glucose is not always available a trial has been done to prevent severe dehydration and death from diarrhea with an oral electrolyte solution without glucose.The efficacy of oral electrolyte solution without glucose was not different from oral glucose electrolyte solution in a double blind study on 60 children with mild and moderate dehydration due to diarrhea.Electrolyte solution without glucose can act as a substitute for glucose electrolyte solution in the therapy of mild and moderate dehydration due to diarrhea.Â